Courseware : learning about plants habitants / Noranirah Ibrahim - Ibrahim, Noranirah (Faculty of Computer and Mathematical Sciences, 2005)
This project is about the development in the multimedia system. This multimedia animation is about the plants characteristic. This thesis will briefly explain on all the procedures involve in developing multimedia system. This thesis wills emphasis on learning about the plants characteristic. The student in the primary school will learn about the plants characteristic through the animation. They will know what category of the selected plants. For example, if the select icon is an orchid, it will links to its physical, habitants and other characteristic. This project can be used as a reference for the primary school student especially Year 4. As the technology emerge, so it will be easily to be learning in school.